2015
DOI: 10.1097/gox.0000000000000242
|View full text |Cite
|
Sign up to set email alerts
|

Video Capture of Plastic Surgery Procedures Using the GoPro HERO 3+

Abstract: Background:Significant improvements can be made in recoding surgical procedures, particularly in capturing high-quality video recordings from the surgeons’ point of view. This study examined the utility of the GoPro HERO 3+ Black Edition camera for high-definition, point-of-view recordings of plastic and reconstructive surgery.Methods:The GoPro HERO 3+ Black Edition camera was head-mounted on the surgeon and oriented to the surgeon’s perspective using the GoPro App. The camera was used to record 4 cases: 2 fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 4 publications
0
38
0
Order By: Relevance
“…The GoPro series of cameras are commercially available ‘action’ cameras typically used for extreme sport photography 39 43. They consist of a high-definition (HD) camera encased in a compact frame that can be strapped to the head or body of the user 42…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The GoPro series of cameras are commercially available ‘action’ cameras typically used for extreme sport photography 39 43. They consist of a high-definition (HD) camera encased in a compact frame that can be strapped to the head or body of the user 42…”
Section: Resultsmentioning
confidence: 99%
“…Five of the nine articles (56%) were primary clinical research articles that evaluated various GoPro devices 35 38 39 42 43. All of these studies found that the technical specifications of the models tested could be adjusted to optimise the quality of picture and video capture such that fine details within the surgical field could be visualised.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The infrared video had the crispest view of the "surgical field," and its wide-angle view replicated the view often seen from cameras mounted on ceilings for ambient room recordingdthis combination of a crisp image and wider-angle view with subjects appearing farther away likely contributed to the mixed opinions regarding anonymity and suggests that the closeness of an image might affect perceptions of anonymity. It also highlights the ability of infrared images to circumvent the "washout effect" of operative lights on surgical videos [13]. Ultimately, the precise balance for any study will depend on the research question and the current state of technology, and we have even found that point-cloud videos can be useful for certain applications, such as workflow tracking or ergonomics assessment.…”
Section: Discussionmentioning
confidence: 96%
“…6 The use of the GoPro camera has been previously used to capture high resolution video of plastic surgery procedures. 7 The use of instructional power-point presentations or videos, followed by live demonstrations and intermittent practice and evaluations has a clear benefit over a single instructional session. 8 While implementation of digital photography, educational and simulation technologies is a big challenge in many training centers, efforts should be made to make their combined use the new standard in dermatologic surgery teaching.…”
Section: Editormentioning
confidence: 99%